(untitled) (Journal of Pharmaceutical Negative Results, 2021)
Background: This study aims to identify socio-demographic variables correlated with anxiety and depression among women recently diagnosed with breast cancer, utilizing the Hospital Anxiety and Depression Scale (HADS). Study Design: A Cross-sectional observational analytical study Place of Study: Department of Psychiatry , General Surgery And GYNAE & OBS Mardan Medical Complex (MMC) from January 05- 2021 to 05-July 2021. Methods and Materials: A sample of 56 newly diagnosed female breast cancer patients aged 18 and above was recruited, excluding those with a history of breast cancer, mental illness, or cognitive impairment. Data analysis involved descriptive statistics, Pearson's correlation coefficient, chi-square tests, and one-way ANOVA using SPSS software. Results: Clinically significant anxiety (HADS-A > 8) was found in 39.3% of patients, while clinically significant depression (HADS-D ≥ 8) was found in 26.8% of patients. Positive correlations were observed between age and HADS-D scores (r = 0.17, p = 0.001). Marital status was significantly associated with both anxiety (X² = 13.017, p = 0.005) and depression (X² = 8.725, p = 0.033), with widowed patients showing higher levels of anxiety and depression. Conclusion: The study underscores the importance of early psychological distress screening in newly diagnosed breast cancer patients, especially among older, widowed, and less educated women. Early detection can facilitate timely intervention, potentially improving mental health outcomes.